2018
DOI: 10.26687/archnet-ijar.v12i2.1530
|View full text |Cite
|
Sign up to set email alerts
|

Re-Thinking Mud House: Countering the Gradual Shift in Traditional Vernacular Architectural Practice in Northern Bangladesh

Abstract: The diversified vernacular architecture in rural Bangladesh is the result of a constant and gradual attempt to maintain sustainability and cultural identity by using knowledge of the local environment. However, factors like natural resource scarcity and economic viability of modern construction techniques is evidently causing a rapid change in the rural landscape. A physical and questionnaire survey carried out in the area under study, namely the village Kaligram in Manda upazilla, Naogaon, revealed that, near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…Islam R et al (2021) also reported that Mud and timber homes emit less CO2 than brick residences, and the embodied carbon of a brick dwelling's basic material is substantially greater than the embodied carbon of wood and mud dwellings. Although N. Monzur (2018) signifies in her research that earth as a building construction material has some disadvantages like reduced durability and compressive strength which affect the applicability of this material. But in spite of the drawbacks, the author suggested some rammed earth and bamboo structure solutions that can validate the concept and virtue of mud houses (Monzur, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Islam R et al (2021) also reported that Mud and timber homes emit less CO2 than brick residences, and the embodied carbon of a brick dwelling's basic material is substantially greater than the embodied carbon of wood and mud dwellings. Although N. Monzur (2018) signifies in her research that earth as a building construction material has some disadvantages like reduced durability and compressive strength which affect the applicability of this material. But in spite of the drawbacks, the author suggested some rammed earth and bamboo structure solutions that can validate the concept and virtue of mud houses (Monzur, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although N. Monzur (2018) signifies in her research that earth as a building construction material has some disadvantages like reduced durability and compressive strength which affect the applicability of this material. But in spite of the drawbacks, the author suggested some rammed earth and bamboo structure solutions that can validate the concept and virtue of mud houses (Monzur, 2018). According to Tariqul Islam K et al, building a brick house is typically based on status, which is the key driver of the shift to manufactured products, and even though most owners of brick and CI sheet buildings are dissatisfied with the thermal comfort, they opted to build brick homes as a demonstration of their better financial standing (Tariqul Islam & Afroz, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…19,005.06 al dividirlo entre el área de la vivienda de 53.33 m 2 tenemos el costo por m 2 construido de S/.356.37 ($107.02). La población vulnerable socioeconómicamente al carecer del cumplimiento de condiciones mínimas de habitabilidad representa un riesgo para su salud física y mental [26]; además [61] indica que no solo se debe construir con un material de construcción más saludable para el medio ambiente, sino que también sea económicamente justificable; por otro lado [14] reconoce que las prácticas sostenibles fortalecen una tecnología de construcción duradera, eficiente y económica en las zonas rurales. Al respecto, podemos indicar que el costo por m 2 construido obtenido es muy bajo y consideramos que favorece a los pobladores de la zona rural en estudio para acceder a la construcción de una vivienda saludable, dadas sus precarias características económicas y de vivienda que poseen.…”
Section: E Evaluación Del Costounclassified
“…A su vez, existe una estrecha relación entre el no contar con viviendas saludables y el origen de problemas mentales, siendo de gran importancia los materiales de construcción, el espacio utilizado y la distribución dentro de la vivienda, por ser aspectos importantes en el desarrollo de estrés [12]. Los beneficios que otorga la implementación de una vivienda saludable están relacionados con su enfoque, así tenemos que, para un ámbito multidimensional, su función es actuar como un eje articulador entre la erradicación de la pobreza y el desarrollo humano [13]; y para una población rural, mejorar las condiciones de salud de las personas, mantener los hábitos saludables y reducir al máximo los riesgos presentes [14] [15] [6]. Un claro ejemplo que ilustra este beneficio, se presenta en el África Sub-Sahariana que mediante sus propuestas implementadas se consiguió disminuir la transmisión de enfermedades por picaduras dentro de la vivienda, regular la temperatura, un mayor confort en la población [11]; y la reducción del 14% de la probabilidad de ser infectado por picaduras en la misma zona debido al cambio de material de construcción "tradicional" por uno más permeable, en este caso se utilizó el bambú [11].…”
Section: Introductionunclassified